Adsorption refrigeration system based on the silica gel-water pair - Sin, Wai Jack (2014)
Adsorption refrigeration system is a system that researchers and scientists are looking into to find a sustainable solution to refrigeration. The system uses environmentally friendly refrigerants and requires lesser electrical energy than the conventional systems.